Belief in God : an introduction to the philosophy of religion - Mawson, T. J. (Clarendon Press ; Oxford University Press, 2005)
T.J. Mawson's highly readable and engaging new introduction to the philosophy of religion offers full coverage of the key issues, from ideas about God's nature and character to arguments for and against His existence. Mawson's conversational style, lively wit, and enlightening examples make Belief in God as pleasurable as it is instructive and thought-provoking. It makes an ideal text for beginning undergraduate courses and for anyone thinking about these most important of questions. Belief in God answers two questions: what, if anything, is it that Jews, Christians, and Muslims are agreeing about when they join in claiming that there is a God; and what, if any, prospects are there for rationally defending or attacking this claim? In the context of a sustained argument for particular answers to these questions, Tim Mawson tackles many of the most prominent topics in the philosophy of religion. He argues that those who believe that there is a God are best interpreted as believing that there is a being who is essentially personal, transcendent, immanent, omnipotent, omniscient, eternal, perfectly free, perfectly good, and necessary, and non-essentially creator of the world and value, revealer of Himself, and offerer of everlasting life.